Where We Stand - Mike Newman; Rashmi Ramaswamy (Oz, 2013)
We are at a unique moment in global history. Against the backdrop of social and economic upheaval, there is growing awareness that our current systems and lifestyles disempower us and are not sustainable. The world’s resources are finite and inequitably distributed. People throughout the world are embracing their inner activist and demanding the right to shape their own destinies.